Assessment of the Lysozyme and Lactoferrin in the Saliva of Vaccinated Individuals against COVID-19 - Hanadi Hafid Abdulkareem Al-Saad/Ahmed Abd Burghal/ Marwan Y. Al-Maqtoofi3 ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
To understand the impact of vaccination against the Coronavirus (Covid-19) on human immunity and systems. This study aimed to determine the concentration of Lysozyme and Lactoferrin in salivary content. The results of Lactoferrin levels in the control group was 12.81, While individuals who were vaccinated 2 doses (less than six months) ago had a lactoferrin rate of 9.65.The results of Lysozyme concentration in control group unvaccinated individuals exhibits a mean concentration of 304.03, compared with those who received one vaccine dose less than 6 months exhibited a higher mean concentration was 338.01, while those vaccinated with two doses less than 6 months was 292.74.